Growth changes of the stout razor clam Tagelus plebeius (Lightfoot, 1786) under different salinities in SW Atlantic estuaries - Addino, Mariana del Sol (2019)
Estuarine abiotic characteristics vary with tidal variations and fresh water input, both driven by climatic conditions and often cyclical climatic events. Estuaries are very productive and bivalves often represent a substantial proportion of the biomass with important ecological role. Salinity fluctuation is often a key environmental factor affecting bivalves shell growth and individual condition index (CI), parameters that in turn can be used to show the quality of the environment for one population. The stout razor clam Tagelus plebeius is an euryhaline filter-feeder species that inhabits sandy-silt tidal flats within a wide salinity range. The objective of this study was to evaluate, by survey sampling and in situ transplant experiments among sites with different salinity, whether shell growth and CI of T. plebeius vary with the salinity regime. We hypothesized a higher growth and CI related to the intermediate salinity. Clams and abiotic parameters were sampled in three estuaries of the northern Argentinian coast with different salinity regimes (Bahía Samborombón (36°19′S), Mar Chiquita coastal lagoon (37°32′S) and Bahía Blanca (38° 47′S)) and in three sites along the salinity gradient of the Mar Chiquita coastal lagoon where the manipulative experiments were also conducted. Shells were more elongated in sites with lower salinity; but the growth rate (k) and the CI were higher in sites with intermediate salinity. Furthermore, clams transplanted from intermediate salinity sites to those with higher or lower salinity showed a disadvantage in shell growth. Considering the scenario of climatic-driven salinity changes in these estuaries and given that T. plebeius is the only native bivalve species in those intertidal zones, having a relevant ecological role and conspicuous fossil presence in Holocene outcrops, our results highlight the relevance of this clam as a valuable target for future studies on conservation biology and paleobiology.